Empowering vital fruit crops with enhanced nutritional contents - Jha, Avinash; Jayswal, D. K.; Shikha, Deep; Kumar, Adyant; Ahmad, Feza (Frontiers in Plant Science, 2025)
Increasing the nutritional value of any crop plant through various Conventional or non-Conventional methods is known as Biofortification. Deficiency of proteins, essential amino acids, vitamins and minerals leads to ailing health and increased vulnerability to various diseases, which in turn lead to uncountable and unpredicted loss in Gross Domestic Product leading to poor economic growth of the country. It is forthcoming and cost-effective approach that will provide a balance of micronutrient deficiency among the people of developing & underdeveloped nations not having the availability to diverse nutritional access. The Biofortified varieties not only provide required calories but also essential nutrients needed for proper growth and development of an individual. It is advantageous in combating malnutrition and hidden hunger by enhancing the micronutrient content of commonly consumed fruits. By increasing essential vitamins, minerals, and beneficial compounds through methods like traditional breeding, genetic engineering, and agronomic practices, biofortified fruits provide a sustainable solution to address deficiencies in regions with limited access to diverse foods. For instance, mango, guava, papaya, and citrus have been improved to offer higher levels of nutrients such as iron, zinc, vitamin C, and beta-carotene. This makes biofortified fruits a cost-effective way to enhance nutrition, particularly for vulnerable populations, helping to reduce the risks associated with hidden hunger and malnutrition. One of the important targets of United Nation is to provide fortified food enriched with important minerals to the targeted undernourished population in different parts of the world. The lack of essential nutrients, notably minerals such as iron (Fe), zinc (Zn), and vitamin A, is one of the main causes of “hidden hunger”, especially in underdeveloped nations. The review covers most of the important aspects of Biofortification in important fruit crops.